Coregistration of magnetic resonance spectroscopy and polysomnography for sleep analysis in human subjects - Masako Tamaki (Elsevier, 2021)
Summary: We developed a protocol for simultaneous magnetic resonance spectroscopy (MRS) and polysomnography (PSG) recordings while subjects are in sleep. The approach is useful to estimate plasticity-stability balances by measuring neurochemical changes in the brain during sleep. We detail the steps needed to minimize artifacts in PSG recordings and the setup and coregistration of MRS data to sleep stages. We also describe useful information for various types of electroencephalogram (EEG) experiments in magnetic resonance imaging (MRI) environments.For complete details on the use and execution of this protocol, please refer to Tamaki et al. (2020b).